The impact of the internet on library and information services / Wan Ab. Kadir Wan Dollah and Mohd Zaihan Hussin - Wan Dollah, Wan Ab. Kadir; Hussin, Mohd Zaihan (Faculty of Information Management, 2010)
Library and information services have been influenced and enhanced by the Internet in many ways, such as methods of information dissemination, scope of information availability and convenience of information accessibility. The Internet has changed reference service by exponentially expanding the universe of available information. Librarians must be able to determine which sites are the best to answer the reference questions. They also have to know how to access, evaluate and navigate Internet sites with the speed, efficiency and comfort level we have long enjoyed with print sources.